Cascaded cuckoo search optimization of router placement in signal attenuation minimization for a wireless sensor network in an indoor environment. Issue 12 (2nd December 2019) - Ghosh, Arnab; Chakraborty, Niladri
ABSTRACT: Optimization of the energy required during data transmission in a wireless indoor area network can be achieved through intelligent router placements to keep the network active for longer and improve the packet delivery ratio. In this work, a cascaded cuckoo search algorithm (C-CSA) approach is implemented for optimal router placement in a wireless indoor area network based on minimization of signal attenuation during data packet transmission through a novel mathematical formulation. The transmission energy for each packet, signal-to-noise ratio and packet error ratio are studied over 50 independent runs of the algorithm. The results are presented with statistical confidence to prove the efficiency of the algorithm. C-CSA provides superior results for data transmission energy and the packet delivery ratio compared to existing algorithms. Physical placement of wireless nodes in a building further establishes the reduction in energy requirement and data packet loss through this optimal router placement strategy.